A mutation in the RIEG1 gene associated with Peters' anomaly. Issue 2 (1st February 1999) - Doward, W; Perveen, R; Lloyd, I C; Ridgway, A E A; Wilson, L; Black, G C M
Abstract : Mutations within the RIEG1 homeobox gene on chromosome 4q25 have previously been reported in association with Rieger syndrome. We report a 3′ splice site mutation within the 3rd intron of the RIEG1 gene which is associated with unilateral Peters' anomaly. The mutation is a single base substition of A to T at the invariant -2 site of the 3′ splice site. Peters' anomaly, which is characterised by ocular anterior segment dysgenesis and central corneal opacification, is distinct from Rieger anomaly. This is the first description of a RIEG1 mutation associated with Peters' anomaly.